A case series to examine whether people with learning disabilities can learn prerequisite skills for cognitive behavioural therapy. (17th January 2018) - Tsimopoulou, Ioanna; Kroese, Biza Stenfert; Unwin, Gemma; Azmi, Sabiha; Jones, Christopher
Abstract: Although cognitive behavioural therapy (CBT) is recommended for the treatment of a number of mental disorders among the general population, the ability of individuals with learning disabilities (LD) to understand CBT concepts and engage in CBT has been questioned.Aims: To examine whether specific prerequisite skills for CBT can be taught to people with LD using a newly developed training intervention and to investigate the acceptability of the intervention.Method: The study adopted a within-subjects case series research design. Quantitative assessment methods were used to evaluate the CBT skills of six adults with mild to moderate LD pre-intervention, following intervention and at 1-week follow-up. Participants were also asked to provide some qualitative feedback about how they had experienced the intervention.Results: The cognitive mediation skills and the ability of most participants to link activating events to emotions increased following intervention training and this improvement was maintained for four of them at follow-up. The feedback of participants regarding the process and content of the task demands was positive.Conclusions: The findings suggest that people with LD can learn some of the skills considered necessary to participate in CBT, such as cognitive mediation. However, further and more robust research is required to substantiate these findings.